Combining covalent bonding interface among different components and controlled orientation of one-dimensional nanofibers for high energy density nanocomposites. (15th August 2022) - Ma, Jiachen; Zhang, Yabin; Miao, Luyang; Zhang, Luqing; Zhang, Shuxiang; Jiang, Xuchuan
Abstract: Dielectric materials with high breakdown strength and excellent dielectric properties have attracted great attention because of their crucial importance in improving energy storage. In this study, a novel method for constructing covalent bonds at the interface of BaTiO3 nanofibers (BT NFs) and fluoropolymer to improve the interfacial adhesion is proposed, in combination with the orientation of one-dimensional BT NFs to improve the energy storage density. It was found that the cross-linked nanocomposites containing covalent bonding interface between thiol-modified BaTiO3 nanofibers (BT-SH NFs) and olefin-modified poly(vinylidene fluoride-chlorotrifluoroethylene) exhibited the supreme compatibility. In addition, the nanocomposite, in which the BT-SH NFs are oriented perpendicular to the electric field, is obtained by stretching, and its breakdown strength is increased by 7.1%. Consequently, the stretched nanocomposite with 5 vol% BT-SH NFs loading achieved a high discharged energy density of 17.1 J/cm 3 . The synergistic effect of cross-linking and stretching treatment accompanied by covalent bonding interface provides a novel strategy for manufacturing high-performance dielectric nanocomposites. Graphical abstract: Covalent bonding interface is constructed between thiol-modified BaTiO3 nanofibers and olefin-modified poly(vinylidene fluoride-chlorotrifluoroethylene), which is combined with the control over nanofiber orientation to enhance the breakdown strength, mechanical properties and energy storage density of nanocomposites. Image 1 Highlights: A novel robust interfacial connection is constructed between BaTiO3 nanofibers and fluoropolymer by covalent bonds. Interfacial covalent bonds have advantages in improving energy storage properties compared to interfacial hydrogen bonds. A simple stretching treatment is used to improve compressive strength and alter the orientation of one-dimensional fillers. The discharged energy storage density of the stretched nanocomposite achieves 17.1 J/cm 3 with a high efficiency of 84.6%.